Alcibiades ΠΟΛΥΤΡΟΠΟΣ: Socratic Philosopher and Tragic Hero? - Fulkerson, Laurel (Histos, 2013)
Alcibiades and Socrates: oil and water, never to mix? Many previous scholars have thought so, finding Alcibiades of interest only as a failed philosophical exemplum, but this article suggests that, at least in the Symposium, Plato presents Alcibiades as the figure in the dialogue closest to Socrates in philosophical attainment. The claim is supported through a series of comparisons, drawn from the dialogue itself and from other ancient sources, particularly Thucydides. Alcibiades can be read as similar to Socrates both in his greatness and in his destiny: to be destroyed by the city that both reared him and underappreciated him. Such a reading opens wider historiographical and even historical perspectives.